Palio sam noge
This film deals with the atrocities of war as portrayed by a film student who spends some time working as a medic during the siege in Sarajevo. One of the duties he performed was to carry amputated limbs to the cremation furnace. The film and the director's story help understand the madness that engulfed Sarajevo and the commotion and tumult that have occurred in the minds of Sarajevans.